HUBUNGAN TINGKAT PENGETAHUAN DENGAN PEMBERIAN ASI EKSKLUSIF PADA IBU YANG BEKERJA DI WILAYAH KERJA PUSKESMAS BULUROKENG - Andi Eka Purnama Sari; Rauly Ramadhani; Darmawansyih (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
Most women work to earn a living outside the home and often leave the family for severalhours each day, which interferes with the breastfeeding process. The increasing female workforce isone of the obstacles in the success of the exclusive breastfeeding program. This is due to the short timeoff from work, lack of workplace support, short rest periods at work (not enough time to expressbreastmilk), and not having room to express breastmilk. This study aims to determine the relationshipbetween the level of maternal knowledge and exclusive breastfeeding of working mothers in theBulurokeng Community Health Center Work Area which was held on January 17, 2020 - February 15,2020. Methods: This research is an analytical survey research using a cross sectional study approach.This study used 125 samples taken using purposive sampling technique which was then measured usinga questionnaire. Results: This study shows that the highest level of mother's education is 58 respondents(46.4%) with a tertiary education level and 4 respondents (3.2%) with an elementary education level.Maternal knowledge was obtained as a result of 10 respondents (8.0%) had a low level of knowledge,22 respondents (17.6%) had a sufficient level of knowledge, and 93% of respondents (74.4%) had agood level of knowledge. There is a significant relationship between the level of maternal knowledgeand exclusive breastfeeding in the Bulurokeng Health Center with a p value of 0.000 (p <0.05)..